Drivers of Pigeon Peas Consumption Among School Aged Children in Central Tanzania - International Crops Research Institute for the Semi-Arid Tropics (International Food Policy Research Institute, 2024)
Data was collected from 138 caregivers of reproductive age (20-49 years) residing in four villages—Laikala, Mlali, Moleti, and Chitego—in Kongwa District, Dodoma Region, Tanzania. The caregivers were from households with school-aged children (5–12 years) and were randomly selected using the random walk sampling method. In each selected household, one caregiver was chosen based on their prior knowledge and consumption of pigeon pea, as well as their willingness to participate in the study. The data collection involved a questionnaire designed to combine the Theory of Planned Behavior (TPB) and the Health Belief Model (HBM). This questionnaire assessed both internal and external factors influencing caregivers' choices regarding pigeon pea consumption for their children. Respondents indicated their level of agreement or disagreement with various statements on a Likert scale, as read by interviewers. This cross-sectional data is intended to provide insights into the factors affecting pigeon pea consumption and is valuable for developing programs and interventions aimed at increasing its intake in the Kongwa District.